Shadows of the PastThe Challenges of Teaching Analytical Writing within the Military - Walters, Jeremy (2023)
The subject matter of this article is the challenges faced by military language students, particularly in the context of analytical writing and the specifics of the military language testing system (STANAG 6001). The main research method used in this paper is a literature review and theoretical analysis in order to discuss and analyse the challenges faced by military language students in the context of analytical writing, as well as potential solutions such as Project-Based Learning (PBL). As such, it does not present original empirical research or data collection. Instead, it draws upon existing research, educational theories, and expert opinions to support its arguments and proposals. A central theme within the paper is that of "educational baggage" and the idea that language learners bring into the classroom their experiences of previous learning environments, be that schools or private courses. Finally, the article suggests that a fully integrated syllabus should be written for military English students that would incorporate all the elements of Project Based Learning and involve all teachers on a given course in a truly integrated manner.
Keywords: andragogy; pedagogy; adult learning; military English; analytical writing; STANAG 6001